Aberrant metabolic processes promote the immunosuppressive microenvironment in multiple myeloma - Lv, Junqiang; Sun, Hao; Gong, Lixin; Wei, Xiaojing; He, Yi; Yu, Zhen; Liu, Lanting; Yi, Shuhua; Sui, Weiwei; Xu, Yan; Deng, Shuhui; An, Gang; et al. (Frontiers in Immunology, 2022)
Multiple myeloma (MM) is still an incurable plasma cell malignancy. The efficacy of immunotherapy on MM remains unsatisfactory, and the underlying molecular mechanisms still are not fully understood. In this study, we delineated the dynamic features of immune cell in MM bone marrow (BM) along with elevated tumor cell infiltration by single-cell RNA sequencing (scRNA-seq), and investigated the underlying mechanisms on dysfunction of immune cells associated with myelomagenesis. We found that immune cells were activated in those patients with low infiltration of tumor cells, meanwhile suppressed with elevated infiltration of MM cells, which facilitated MM escaping from immune surveillance. Besides PD-1, abnormal expression of PIM kinases, KLRB1 and KLRC1 were involved in the defect of immune cells in MM patients. Importantly, we found aberrant metabolic processes were associated with the immunosuppressive microenvironment in MM patients. Disordered amino acid metabolism promoted the dysfunction of cytotoxicity CD8 T cells as well as lipid metabolism disorder was associated with the dysregulation of NK and DCs in MM. As metabolic checkpoints, PIM kinases would be potential effective strategies for MM immunotherapy. In summary, redressing the disordered metabolism should be the key points to get promising effects in immune-based therapies.